Rethinking Preschool Education in Rural Turkey: Parents' Lived Experiences of Access, Quality, and Inequality - Dikmen, Melih; Gokalp, Ayse Can (Springer, 2026)
Early childhood education in Turkey has expanded considerably in recent years, particularly in rural areas; however, increased physical access has not always translated into improved educational quality. While prior research has largely focused on enrollment rates and policy implementation, less attention has been paid to how rural parents themselves experience and interpret preschool education in everyday life. This study examines rural parents' lived experiences and perceptions of preschool education, with a focus on access, quality, and inequality. Using a phenomenological qualitative design, in-depth interviews were conducted with eleven parents residing in a rural district in eastern Turkey. Data were analyzed through qualitative content analysis, capturing both manifest meanings and underlying experiential patterns. Five interrelated themes emerged: experiencing preschool as a developmental and protective space; experiencing preschool education as a transformative developmental process; experiencing access and adequacy in everyday preschool life; experiencing inequality through spatial difference; and experiencing expectations and aspirations for more holistic, creative, and locally responsive preschool environments. Findings indicate that parents view preschool education as a critical context for children's social-emotional development, communication skills, and preparation for primary school. Although access to preschool services was generally perceived as adequate, parents expressed persistent concerns regarding material resources, infrastructural limitations, and restricted learning opportunities. Rural-urban inequality was experienced not simply as a difference in facilities, but as a spatially mediated condition shaping children's developmental opportunities and future trajectories. These findings highlight the importance of moving beyond access-oriented policies toward quality-focused and context-sensitive approaches in rural early childhood education.
Keywords: Preschool education; Parental perceptions; Rural-Urban inequality; Early childhood education